Penyuluhan Agama Dalam Pengembangan Masyarakat Islam: Studi Peran Penyuluh Agama Dalam Pengembangan Masyarakat Islam - Makmun, Fariza; Faizal, Faizal (BINA' AL-UMMAH, 2021)
This article discusses the role of Islamic preachers in the development of Islamic society. Practically, religious preaching is one of the methods in developing moslem society. Islamic preachers in terms of community development are called facilitators who have a role as the subject of Islamic preaching (da'wah). This study is a conceptual study which is done by elaborating the concepts of Islamic community development through extension of programs discussed in various literatures. The findings of this study indicate that as a subjects of Islamic preaching (dakwah) as instructors or facilitators play multiple roles; as facilitator, mediator, educator, communicator, dynamist, motivator and stabilizer. The role of the Islamic  instructors is actually very broad and complex. The main role of the Islamic instructors in the development of Islamic society is based on the educative role.